X-efficiency and economies of scale in pension fund administration and investment - Gosse A.G. Alserda; Jacob A. Bikker; Fieke (S.G.) van der Lecq (Utrecht University, Utrecht University School of Economics, Tjalling C. Koopmans Research Institute, 2017)
Pension funds' operating costs come at the cost of benefits, so it is crucial for pension funds to operate at the lowest cost possible. In practice, we observe substantial differences in costs per member for Dutch pension funds, both across and within size classes. This paper discusses scale inefficiency and X-inefficiency using various approaches and models, based on a unique supervisory data set, which distinguishes between administrative and investment costs. Our estimates show large economies of scale for pension fund administrations, but modest diseconomies of scale for investment activities. We also found that many pension funds have substantial X-inefficiencies for both administrative and investment activities. The two kinds of inefficiency differ across types of pension funds. Therefore, most pension funds should be able to improve their cost performance, and hence increase pension benefits
Keywords: 330; Efficiency; operating costs; cost elasticity; stochastic cost frontier analysis; optimal scale